Gallium and indium complexes with isoniazid-derived ligands: Interaction with biomolecules and biological activity against cancer cells and Mycobacterium tuberculosis - Leitao, Renan C.F. (2023)
Gallium and indium octahedral complexes with isoniazid derivative ligands were successfully prepared. The ligands, isonicotinoyl benzoylacetone (H2L1) and 4-chlorobenzoylacetone isonicotinoyl hydrazone (H2L2), and their respective coordination compounds with gallium and indium [GaL1(HL1)] (GaL1), [GaL2(HL2)] (GaL2), [InL1(HL1)] (InL1) and [InL2(HL2)] (InL2) were investigated by NMR, ESI-MS, UV–Vis, IR, single-crystal X-ray diffraction and elemental analysis. In vitro interaction studies with human serum albumin (HSA) evidenced a moderate affinity of all complexes with HSA through spontaneous hydrophobic interactions. The greatest suppression of HSA fluorescence was caused by GaL2 and InL2, which was associated to the higher lipophilicity of H2L2. In vitro interaction studies with CT-DNA indicated weak interactions of the biomolecule with all complexes. Cytotoxicity assays with MCF-7 (breast carcinoma), PC-3 (prostate carcinoma) and RWPE-1 (healthy human prostate epithelial) cell lines showed that complexes with H2L2 are more active and selective against MCF-7, with the greatest cytotoxicity observed for InL2 (IC50 = 10.34 ± 1.69 μM). H2L1 and H2L2 were labelled with gallium-67, and it was verified that 67GaL2 has a greater lipophilicity than 67GaL1, as well as higher stability in human serum or in the presence of apo-transferrin. Cellular uptake assays with 67GaL1 and 67GaL2 evidenced that the H2L2-containing radiocomplex has a higher accumulation in MCF-7 and PC-3 cells than the non-halogenated congener 67GaL1. The anti-Mycobacterium tuberculosis assays revealed that both ligands and metal complexes are potent growth inhibitors, with MIC90 (μg mL−1) values observed from 0.419 ± 0.05 to 1.378 ± 0.21.